2004
DOI: 10.1021/ac040094l
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Poly(methyl methacrylate) Capillary Electrophoresis Microchips for Protein and Peptide Analysis

Abstract: Polymeric materials have emerged as appealing alternatives to conventional inorganic substrates for the fabrication of microscale analytical systems; however, native polymeric surfaces typically require covalent modification to ensure optimum biocompatibility. 2-Bromoisobutyryl bromide was immobilized on poly(methyl methacrylate) (PMMA) substrates activated using an oxygen plasma. Atom-transfer radical polymerization was then performed to graft poly(ethylene glycol) (PEG) on the PMMA surface. PMMA microcapilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(180 citation statements)
references
References 51 publications
(78 reference statements)
6
169
0
Order By: Relevance
“…Other permanent coatings were prepared with dextran on silanized fused-silica capillary [79], hexamethyl disiloxane plasma polymerized with 2.3-epoxy-1-propanol on glass microchip [80,81], fluorinated aromatic hydrocarbons attached to PDMS by chemical vapor deposition [82], trimethoxysilane-modified poly(dimethyl acrylamide) [83], poly(vinyl alcohol) thermally immobilized on oxygen plasma-pretreated PDMS [84], and PEG grafted on Plexiglas surface [85].…”
Section: Static Wall Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other permanent coatings were prepared with dextran on silanized fused-silica capillary [79], hexamethyl disiloxane plasma polymerized with 2.3-epoxy-1-propanol on glass microchip [80,81], fluorinated aromatic hydrocarbons attached to PDMS by chemical vapor deposition [82], trimethoxysilane-modified poly(dimethyl acrylamide) [83], poly(vinyl alcohol) thermally immobilized on oxygen plasma-pretreated PDMS [84], and PEG grafted on Plexiglas surface [85].…”
Section: Static Wall Coatingmentioning
confidence: 99%
“…A number of CE steps and components that are used in fused-silica capillaries have been transferred and successfully tested on a microchip including preconcentration on porous silica membrane [22,23], automated derivatization [29], microreactor with immobilized proteases and other proteins [181,182], UV detector [183,184], chemiluminescence detector [34,185], multiwavelength LIF detector [186], UV LIF detector [98], wall coatings [82,85], affinity CE [129], CIEF [80], and sheathless electrospray for MS [113,114].…”
Section: Electrophoresis On-chipmentioning
confidence: 99%
“…The two networks are linked by the fluidic bridges (7). (b) Control level: the control level is composed of a single closed channel (8) fanning into eight branches to form the pressure valves (9) 20 PSI in the control line was found to be appropriate to completely and reversibly close the eight valves without disrupting the flow in the outlet channels (Fig. 3).…”
Section: Engineering Of Pressure Valvesmentioning
confidence: 99%
“…Many research groups have investigated chemical surface modifications of various polymeric materials to limit the effects of NSA. [6][7][8][9][10][11][12] In particular, surface modifications of poly(dimethylsiloxane) (PDMS) have been extensively explored as it is currently the preferred polymer for biochip fabrication. [13][14][15][16][17][18][19][20][21] Despite many advantages, PDMS is notorious for its high native hydrophobicity and its tendency to rapidly adsorb biological materials.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [205] also reported the use of ATRP for microchip surface modification. They grafted PEG on a PMMA microchip after the immobilization of a typical ATRP initiator, 2-bromoisobutyryl bromide.…”
Section: Atrpmentioning
confidence: 99%